Diagnosis of Epidermolysis Bullosa Acquisita: Multicentre Comparison of Different Assays for Serum Anti-type VII Collagen Reactivity - Maike M. Holtsche; Nina van Beek; Takashi Hashimoto; Giovanni Di Zenzo; Detlef Zillikens; Catherine Prost-Squarcioni; Matthias Titeux; Alain Hovnanian; Enno Schmidt; Stephanie Goletz (Medical Journals Sweden, 2021)
Epidermolysis bullosa acquisita is a pemphigoid disease characterized by autoantibodies against type VII collagen. This study compared the sensitivity and specificity of 6 diagnostic assays: type VII collagen non-collagenous domains enzyme-linked immunoassay (NC1/2 ELISA) (MBL, Nagoya, Japan); type VII collagen NC1 ELISA (Euroimmun, Lübeck, Germany); indirect immunofluorescence (IF) microscopy test based on the expression of recombinant NC1 in a human cell line (NC1 BIOCHIP®; Euroimmun); full-length recombinant type VII collagen ELISA; immunoblotting with full-length type VII collagen in the extract of human dermis; and immunoblotting with recombinant NC1. Immunoblotting with recombinant NC1 showed a sensitivity of 93.1% and specificity of 100%, followed by NC1 BIOCHIP® (sensitivity, 89.1%; specificity, 100%), immunoblotting with human dermis (sensitivity, 87.1%; specificity 100%), NC1-ELISA (sensitivity 82.2%; specificity 98.6%), NC1/NC2 ELISA (sensitivity 88.1%; specificity 93.3%), and full-length type VII collagen ELISA (sensitivity 80.2%; specificity 93.8%).